Mafaahim wa Afkaar An-Naqd al-Adabi ‘inda al-Qadhi al-Jurjani - Mahdiyyah, Syahda A’immatul; Hidayat, Moh. Wakhid (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Abu Hasan Ali bin Abdul Aziz al-Husain bin Ali bin Ismail or better known as al-Qadhi al-Jurjani is one of the critics born during the Abbasid period, where in the period before that literary criticism was still subjective until the Abbasid period the critics began to give birth to their respective concepts and thoughts about literary criticism. This article aims to discuss the concepts and thoughts of literary criticism initiated by one of the Arab critics, namely al-Qadhi al-Jurjani. This research uses a qualitative descriptive method based on library research. Data were collected using the method of reading and recording techniques from data sources in the form of books by al-Qadhi such as the book al-Wasathah baina al-Mutanabbi wa Khusumihi and also other references related to the thoughts and concepts of al-Qahdi regarding literary criticism. After the data is collected, it is analysed using data reduction, data display (presentation of data), and conclusions which are then presented with systematic language. The results showed that some concepts or thoughts and ideas of literary criticism according to Al-Qadhi are the concept of how to obtain or make poetry and the difference of poetry, the concept of Amud Shi'ri, the concept of modern poets (muhaditsun) and the past (qudama'), the concept of critics, and the concept of literary theft or plagiarism.